Perspectives on metal–organic frameworks with intrinsic electrocatalytic activity. Issue 29 (23rd March 2017) - Solomon, Marcello B.; Church, Tamara L.; D'Alessandro, Deanna M.
Abstract : This highlight article focuses on the rapidly emerging area of electrocatalytic metal–organic frameworks (MOFs) with a particular emphasis on those systems displaying intrinsic activity. Abstract : This highlight article focuses on the rapidly emerging area of electrocatalytic metal–organic frameworks (MOFs) with a particular emphasis on those systems displaying intrinsic activity. Three electrocatalytic conversion processes are discussed, including CO2 reduction, the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), as well as a selection of other relevant examples. The scope of our discussion encompasses aspects of MOF structure that are key to their function, performance characteristics such as stability and selectivity, together with methods for interfacing MOFs with surfaces. Key challenges that have emerged are highlighted in addition to opportunities that are relevant to the field in the design of more stable, selective and robust electrocatalysts for a range of industrial processes.